ANALISIS PERBANDINGAN KINERJA LOAD BALANCING MENGGUNAKAN METODE PCC DAN NTH - Jamil, Muhlis; Santosa, Santosa; Hamid, Mustamin (Program Studi Pendidikan Teknologi Informasi, 2023)
The need for internet access is not just for chatting and browsing, but has reached online games and video streaming. High access requirements result in an unbalanced traffic load and a decrease in access speed. Load balancing is a technique for distributing traffic loads on two or more connection lines in a balanced way, so that traffic can run optimally, maximize throughput, minimize response time and avoid overload on one of the connection lines. PCC results on the throughput (bps) test, the throughput value on the first PCC test by running the speedtest the throughput value (bps) is obtained at 665k, the second test by downloading the zoom application the throughput value (bps) is obtained at 412k, the third test by playing youtube the throughput value ( bps) was obtained at 816. While the packet loss on the first PCC test the packet loss value (%) was obtained at 0.4%, the second test the packet loss value (%) was obtained at 1.8%, the third test the packet loss value (%) was obtained at 2.3%. The NTH results on the throughput test, the throughput value on NTH The first test by running the speedtest the throughput value (bps) is obtained at 184k, the second test by downloading the zoom application the throughput value (bps) is obtained at 495k, the third test by playing youtube the throughput value (bps) is obtained of 829k. While the packet loss on the first test NTH packet loss value (%) was obtained at 1.6%, the second test the packet loss value (%) was obtained at 2.2%, the third test the packet loss value (%) was obtained at 3.0%..